The encyclopedia of North American Indians / vol-IX Ross,John-Trail of Broken Treaties - Birchfield, D. L., 1948- (New York : Marshall Cavendish, 1997)
A comprehensive reference work on the culture and history of Native Americans.
v. 1. Abenaki-Baskets -- v. 2. Beadwork and beadworkers-Cherokee Phoenix -- v. 3. Cheyenne-Delaware -- v. 4. Deloria, Ella-General Allotment Act -- v. 5. Georgia-Inuit -- v. 6. Iowa Indians-McIntosh, William -- v. 7. McNickle, D'Arcy-Ojibwe -- v. 8. Ojibwe literature, contemporary-Rosebud Reservation -- v. 9. Ross, John-Trail of Broken Treaties -- v. 10. Trail of Tears-Zuni -- v. 11. Appendices and indexes.
Includes bibliographical references and indexes.
Keywords: Indians of North America -- Encyclopedias, Juvenile; Indians of North America -- Encyclopedias